Aproximações e distanciamentos na educação do campo: dos documentos oficiais aos livros didáticos - componente curricular Ciências - Silva, Edneide Maria Ferreira da (2020)
The research was carried out within the Education Research Line in Science and Mathematics Teaching of the Graduate Program in Education at the Federal University of Uberlândia. The theme is inserted in the field of studies that deal with field education and textbooks, in this teaching modality, focusing on those that present the curricular component (discipline) Sci-ences. The research problem was constituted from the concern about the approximations and distances between the principles and orientations proposed by the official documents that supported the notices (2011 and 2014) of the National Program of the Didactic Book of the Field (NPDB Field - 2014 and 2016) and the one presented in the texts of the Science curricu-lar component of the collections approved by the aforementioned public notices. The general objective was defined: to analyze the distances and approximations between the established by the official documents that regulate the Education of the Field, the aforementioned notices and the texts of the curricular component Sciences of the textbooks approved in the editions of the NPDB Field, of 2013 and 2016, and, as specific objectives: indicate the propositions and principles presented by the official documents and edicts for the selection of textbooks for the NPDB Field (2013 and 2016); identify in the texts of the Science curricular compo-nent, which integrate the analyzed books, how the determinations and guiding principles for Rural Education are presented, and, raise, in these texts, the themes and places where it is pos-sible to locate the principles and determinations for the Rural Education, proposed by the source documents of the study. From a methodological point of view, it was a descriptive-qualitative research, using bibliographic and documentary sources. In the analytical procedure, descriptive procedures and documentary analysis were used. References from the critical field of education, field education and the Science textbook were used. The thesis that is defended is that, for the scope and implementation, via Science textbooks, of the assumptions and prin-ciples presented by the official documents and social movements of the people of the country-side, their contents, methodologies and curricular proposals must be guided in the dialogue interdisciplinary, in an idea of Sciences supported by the dialogue between cultures and sci-ence, in the rupture of the unique and universal idea of subject of the field, intimately linked to the quotidian, the sociocultural diversity and the differences in all its extension. Such com-pleteness of approach was not verified in the texts of the Sciences curricular component ana-lyzed, since they meet in a timely manner as established by official documents. Thus, the in-vestigated Sciences curricular component produces approximations when, in specific places, they portray or dialogue with the subject of the field and their socio-cultural diversity, and, in others, distances when they present themes and contents unrelated to these subjects and their daily lives.